Analisis Manfaat Dan Urgensi Dana Pelangakahan Dalam Perkawinan Suku Jawa Dan Suku Sasak - Syafrina Monica, Eka; Hanum Harahap, Herlina (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
There are differences in terms of the naming and practice of marriage initiation funds between the Javanese and Sasak tribes. There are different concepts between the two in terms of practice, of course due to the different social and cultural backgrounds between the Javanese and Sasak tribes. The benefits and urgency are the benchmarks for how important it is to do it and become a custom. In this research, the research methodology used is library research and uses a sociological approach to help the author analyze the benefits and urgency of marriage transition funds. The results found that the funds for marriage steps between the Javanese and Sasak tribes had similarities and differences. The similarity is that this is done to honor or respect and ask permission from the sibling being stepped on, and the step can be in the form of money or other objects. Meanwhile, the difference is in practice, in the Javanese tribe, the person who is stepped over is either an unmarried female sibling or male sibling who is given the step, whereas in the Sasak tribe only unmarried older brothers are given the step. The Javanese tribe's step process has more procedures than the Sasak tribe. The Sasak tribe's concept of giving a handover is from the prospective husband to the unmarried brother of the prospective wife, whereas in the Javanese tribe the handover can tend to be from the younger sibling to the sibling's older brother/sister. The benefit and urgency is to respect each other and avoid misunderstandings, as well as carrying out the customs and culture of each tribe so that they are preserved and the stepping goods are only an entertainment for the person who steps over.